Antidiabetic Medicinal Plants Used by the Basotho Tribe of Eastern Free State: A Review - Fatai Oladunni Balogun; Natu Thomas Tshabalala; Anofi Omotayo Tom Ashafa (Journal of Diabetes Research)
Diabetes mellitus (DM) belongs to the group of five leading important diseases causing death globally and remains a major health problem in Africa. A number of factors such as poverty, poor eating habit, and hormonal imbalance are responsible for the occurrence of the disease. It poses a major health challenge in Africa continent today and the prevalence continues to increase at an alarming rate. Various treatment options particularly the usage of herbs have been effective against diabetes because they have no adverse effects. Interestingly, South Africa, especially the Basotho tribe, is blessed with numerous medicinal plants whose usage in the treatment of DM has been effective since the conventional drugs are expensive and often unaffordable. The present study attempted to update the various scientific evidence on the twenty-three (23) plants originating from different parts of the world but widely used by the Sotho people in the management of DM. Asteraceae topped the list of sixteen (16) plant families and remained the most investigated according to this review. Although limited information was obtained on the antidiabetic activities of these plants, it is however anticipated that government parastatals and scientific communities will pay more attention to these plants in future research.